Editorial: Current proceedings in magnetocardiology—past, present, future - Park, J-W.; Dischl, D.; Aschbacher, K.; Kranz, D.; Rieß, J. C.; Kim, S-W.; Brachmann, J.; Treskatsch, S.; Heidecker, B.; Landmesser, U.; Wessel, N. (Frontiers in Cardiovascular Medicine, 2024)
This special issue on "Current Proceedings in Magnetocardiology -past, present, future" explores the latest advancements and applications of magnetocardiography (MCG) in clinical settings. The included papers cover a wide range of topics, from the use of MCG in diagnosing and monitoring cardiac conditions like myocarditis and cardiomyopathies to the technological advancements enabling unshielded MCG use in everyday clinical practice. Each study contributes to our understanding of MCG's diagnostic capabilities, offering insights into its non-invasive nature, efficiency, and potential for enhancing cardiac care. The editorial describes the newly discovered magnetoionography (MIG), which for the first time enables us to non-invasively measure the membranous ion currents of action potential as well as the subcellular Ca2+ transient. Finally, the editorial is rounded off with the vision of the future that we can and must expect when artificial intelligence (AI) is applied to MCG/MIG.